A tuberculose em Porto Alegre, 1896 a 1924: um estudo de mortalidade - Medeiros, João Gabriel Toledo (Universidade do Vale do Rio dos Sinos, 2015)
This master thesis has as object of study tuberculosis in Porto Alegre in the period from 1896 to 1924, through a history of health and disease view. The period is marked by the positivist ideology that guided the politicians who ruled the State and consequently the municipality. Therefore, we analyze the state position regarding the disease and its efforts to combat it, besides establishing, through a quantitative method, the profile of individuals who died from tuberculosis in the period, and also the treatments. They were used in this work Board reports of Hygiene and President of the Province and the state, books of death records of the Santa Casa de Porto Alegre, Cemitério da Tristeza, reports by the providers of Santa Casa and newspapers of the time.
Keywords: Tuberculose; História da doença e da saúde; Porto Alegre; Tuberculosis; Disease and health history; ACCNPQ::Ciências Humanas::História